Total Quality Management In Network Management & Operations Department Of Telekom Malaysia - Hua, Chan Keng (2000)
The purpose of this study was to investigate the practices of total quality management in Network Management & Operations (NMO) department of Telekom Malaysia. This study also covered the effectiveness of ISO 9002 standard implementation in NMO. In additi